Pathogenicity of Entomophatogenic Fungi Lecanicillium lecanii Against Predator Insect Menochilus Sexmaculatus - Hadi, Mochammad Syamsul; Taufiqurrahman, Achmad Fitriadi; Choliq, Fery Abdul; Istiqomah, Istiqomah; Karindah, Sri (PLANTA TROPIKA: Jurnal Agrosains (Journal of Agro Science), 2020)
Lecanicillium lecanii is an insect pathogenic fungus that is often used for pest control and has a wide range of hosts. The L. lecanii is capable of infecting several types of host insects including the Order Orthoptera, Hemiptera, Lepidoptera, Thysanoptera and Coleoptera. The extent of this fungus host range was feared to have a negative effect on predator insects Menochilus sexmaculatus. This study aims were to determined the pathogenicity of the fungus L. lecanii against the imago predatory beetle M. sexmaculatus, to know how the predation ability and the number of eggs fecundity of Imago M. sexmaculatus after application L. lecanii. The research was arranged in Randomized Block Design with 4 replications. The conidia density of L. lecanii used were 106, 107, 108, 109 conidia/ml, 1 ml / l of lufenuron insecticide as positive control and sterile distilled water as negative control. The research showed that the mortality percentage of M. sexmaculatus due to L. lecanii application is low and medium. The L. lecanii was not affected for preying ability on imago M. sexmaculatus but gave effect to the number of eggs fecundity of imago M. sexmaculatus.